Seasonal Variation in the Epibenthic Feeding Habits of Hilsa Shad (Tenualosa ilisha) in the Upper Meghna River Estuary, Bangladesh - Md. Jahangir Sarker; Pallab Kumer Sarker; Lawrence B. Cahoon; Afsana Kabir Dipty; Md. Abul Bashar; Md. Monjurul Hasan; Yahia Mahmud; Md. Milon Sarker (Fishes, 2023)
Seasonal changes in feeding habits of hilsa (Tenualosa ilisha) were studied monthly in 2019 in the upper Meghna estuary, Bangladesh, through gut content analyses. Tychoplanktonic diatoms followed by copepods were abundant in all months and size groups of hilsa. The inverse relationship between niche breadth and relative length of the gut revealed hilsa consume a variety of food at their early stages while their feeding habit changes towards diatoms during the adult stage with the development of gill rakers. Young hilsas prefer mostly tychoplanktonic diatoms (Aulacoseira sp., Triceratium sp., Nitzschia sp., Synedra sp., and Coscinodiscus sp.) and copepods (Pseudodiaptomus sp.). However, adult hilsas rejected Aulacoseira sp. during their spawning season. Ingested sand grains correlated with tychoplankton, revealing their food value from epipelic microalgae and bacteria clinging to them and epibenthic foraging by young hilsas. Thus, this study revealed that young hilsas primarily feed on tychoplanktonic diatoms and copepods from water and near bottom of the upper Meghna estuary during January to June while later stages with the development of gill rakers allow hilsas to feed on planktonic diatoms. Epibenthic feeding needs to be considered more fully in evaluating the biology of hilsa and, perhaps, other clupeids, and in evaluating possible human impacts on this foraging habitat.